Studies on in vitro Radical Scavenging Potentials of Methanol Leaf Extract of Ficus sur and its Fractions - Obi, Kelechi Nwabueze; Onyeike, Eugene Nwaogwugwu; Anacletus, Francis Chukwuma (Free Radicals and Antioxidants)
Background: In many rural areas of Nigeria, Ficus sur is traditionally used in the management of many diseases some of whose pathogenesis implicate free radicals. Objectives: To determine the phenolic contents and the in vitro radical scavenging activities of methanol extracts of Ficus sur (MEFS) and its hydromethanol (HMFS), ethyl acetate (EAFS) and hexane (HFFS) fractions. Materials and Methods: The leaves of Ficus sur were air dried, extracted with absolute methanol, and then partitioned sequentially with hexane and ethyl acetate. The phenolic contents of the parent extract and the fractions were determined. The scavenging activities of the extracts towards 1,1diphenyl-2-picryl hydrazyl (DPPH), hydroxyl, propagating lipid peroxyl and nitric oxide radicals were examined quantitatively. Results: Total phenol, flavonols and flavonoids were high in MEFS, moderate in EAFS and low in HFFS. The extracts scavenged DPPH radical (IC50 = 42.35± 3.55- 169.43 ± 16.43 , hydroxyl radical (IC50 = 55.58 ±8.16- 318.33± 14), peroxyl radical (IC50 = 60.33± 13.8- 219± 36.44 µg/ml) and nitric oxide radical (IC50 = 41.94 ±6.65- 210.5 ± 11.3 µg/ml) in a dose-dependent manner. The flavonoid contents of the extracts inversely correlated with the IC50 values of free radical scavenging activities. Overall, the radical scavenging abilities of MEFS and its fraction follow the order: MEFS> HMFS> EAFS> HFFS. Conclusion: Hence, it may be concluded that extracts that have higher phenolic contents are superior to those with lower phenolic contents in radical scavenging activities, which cement the fact that, indeed, phenolics are largely responsible for the invitro antioxidant activities of the plant extracts.
Keywords: Ficus sur; Antioxidants; DPPH; Phenolics; Radicals; Scavenging